2020
DOI: 10.3389/fonc.2020.579379
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Variation in Familial Cancer as Suggested by Family History, Multiple Primary Cancer, Age at Onset, and Sex Ratio Associated With Upper, Middle, and Lower Third Esophageal and Gastric Cardia Carcinoma

Abstract: Background: In China, esophageal squamous cell carcinoma (ESCC) and gastric cardia adenocarcinoma (GCA) differ in terms of multiple primary cancer (MPC) and male-tofemale sex ratio (MFSR). Methods: We studied site-specific variation in familial cancer by comparing family history (FH), MPC, age at onset (AO), and MFSR among 8768 patients with ESCC/GCA. Results: ESCC/GCA patients with a positive FH are associated with a significantly higher rate of MPC and a younger AO than those without (sex-specifically: MPC 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, relying solely on the TNM staging system has obvious limitations, as it lacks important variables such as age, differentiation grade, and other influential factors. Therefore, it is not suitable for individualized analysis 7,8 . Multiple studies have demonstrated that the log odds of positive lymph nodes (LODDS) are superior to the N stage alone in determining lymph node metastasis and providing accurate prognostic assessments for patients with cancer 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, relying solely on the TNM staging system has obvious limitations, as it lacks important variables such as age, differentiation grade, and other influential factors. Therefore, it is not suitable for individualized analysis 7,8 . Multiple studies have demonstrated that the log odds of positive lymph nodes (LODDS) are superior to the N stage alone in determining lymph node metastasis and providing accurate prognostic assessments for patients with cancer 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not suitable for individualized analysis. 7 , 8 Multiple studies have demonstrated that the log odds of positive lymph nodes (LODDS) are superior to the N stage alone in determining lymph node metastasis and providing accurate prognostic assessments for patients with cancer. 9 , 10 In line with this, a nomogram is a graphical calculation instrument based on statistical models that can predict the likely outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proportion of people who drank was significantly higher in SMPEEC than in SEEC (Table 1). A possible correlation between alcohol consumption and multiple primary esophageal cancers has been reported by Saeki H and Denggui Wen (19,20). These authors reported that excessive smoking and alcohol consumption were risk factors associated with multiple primary carcinomas, and the mechanism of the carcinoma manifestation involved increased sensitivity of genes to the environment.…”
Section: Discussionmentioning
confidence: 82%
“…Upper esophageal LULs had a 9.72‐fold risk of being detected as SDA as compared with those in the lower esophagus in subjects with a family history of ESCC. (ii) Studies have shown that the proportion of ESCC patients with a positive ESCC family history gradually increased from the lower, middle, to upper esophagus, suggesting a higher genetic susceptibility in the upper esophagus 14 . (iii) ESCCs of the upper esophagus have a worse prognosis, 11 suggesting that tumors in different locations of the esophagus have different biological behaviors.…”
Section: Discussionmentioning
confidence: 99%